Expansion Strategy PT. Crown Pratama to Competitive Packaging Market of Bali - Champio, Champio; Toha, Mohammad (The Indonesian Journal of Business Administration, 2014)
Abstract – PT. Crown Pratama is a packaging company for the needs of hotel, restaurant and cafe. they want to expand to Bali because the amazing growth of hotels, restaurants and cafes. Besides the competitive packaging competition in Bali has a market leader, PT. Crown Pratama should have a strategy in order to grab and increase the sells unit. The right attack strategy is needed in order to attack the main competitor. The objective of the final project is to know key success factors and appropriate attack strategy for PT. Crown Pratama in Bali. Business exploration is done by define internal and external analysis. Internal analysis tool is used SWOT analysis, while external analysis tool is used Porter’s Five Forces. Strategy is formulated by conducting a simple qualitative method market research in order to get the key success factors. The result of interviewed 10 customers from different industry segment are 6 key success factors. Company and competitor characteristic are also determined to know the strength and weakness of both. The result of this research are suggested company to use flanking attack as appropriate attack strategy for PT. Crown Pratama because there is already a strong market leader in Bali. Focus to grab the customer where the competitor not focused on their strengths in customer segment or geographical area Keywords : business strategy, packaging, key success factors, attack strategy